Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/jcm11123382
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antihyperglycemic Drugs and Diet on Erectile Function: Results from a Perspective Study on a Population with Prediabetes and Diabetes

Abstract: Background. The purpose of this study was to evaluate the effect of diet and antihyperglycemic drugs on erectile dysfunction (ED) in a setting of subjects affected by diabetes mellitus (DM) or preDM. Methods. This is a prospective observational study on 163 consecutive subjects with preDM or DM. All patients have undergone a medical evaluation (age, Body Mass Index (BMI), family history of DM, duration of DM, smoking, physical activity, dyslipidemia, cardiovascular comorbidities, and testosterone and HbA1c lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
2
10
0
3
Order By: Relevance
“…This result was in accordance with other reports, which highlighted that the IIEF-5 score is higher in patients on therapy with new antidiabetic drugs, in particular with GLP1-Ras, compared to the scores obtained by patients treated with insulin or old antidiabetic drugs [ 9 , 37 ]. So far, the studies conducted on the impact of GLP1 and SGLT2i on male sexual function have mostly been conducted on mouse models, but the results seem to be encouraging [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…This result was in accordance with other reports, which highlighted that the IIEF-5 score is higher in patients on therapy with new antidiabetic drugs, in particular with GLP1-Ras, compared to the scores obtained by patients treated with insulin or old antidiabetic drugs [ 9 , 37 ]. So far, the studies conducted on the impact of GLP1 and SGLT2i on male sexual function have mostly been conducted on mouse models, but the results seem to be encouraging [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…The authors observed that patients treated with liraglutide showed a significant improvement in erectile function compared to the group that received only testosterone and metformin; therefore, this finding underlines a potential protective effect of GLP-1a on sexual function. Similar results were observed by Defeudis et al [ 18 ], who found in a prospective observational study that patients treated with GLP-1a showed a better erectile function than patients treated with insulin; the results were also confirmed after adjustment for age and duration of DM. Nevertheless, diabetes is closely related to cardiovascular disease [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…Finally, two sensitivity analyses were additionally performed to assess the robustness of our findings. In the first sensitivity analysis, we excluded participants taking medicines that potentially affect erectile function, including antidepressants (42), antipsychotics (43), antihyperglycemic agents (9,44), sex hormones and corticosteroids (45). In the second sensitivity analysis, a stricter criterion of ED was used.…”
Section: Discussionmentioning
confidence: 99%